Comparison of a pressure-sensing sheath and radial arterial line for intraoperative blood pressure monitoring in neurointerventional procedures. (27th February 2018) - Froehler, Michael T; Chitale, Rohan; Magarik, Jordan A; Fusco, Matthew R
Abstract : Purpose: The efficiency of neuroendovascular procedures may partly depend on the time devoted to placement of a radial arterial line (RAL) for intraoperative blood pressure monitoring. An alternative approach is to use a pressure-sensing sheath (PSS) that serves to provide invasive blood pressure monitoring without requiring a separate procedure for placement. We compared the use of a RAL versus PSS and assessed procedure time, anesthetist and patient satisfaction, and cost. Methods: We performed a single-center, prospective, blockwise, comparative trial of procedure start time using traditional RAL placement versus the EndoPhys PSS for invasive blood pressure monitoring. Endpoints included time from room arrival to groin puncture, patient and anesthetist satisfaction ratings, and costs associated with RAL placement. Results: Twenty patients were enrolled in the PSS+RAL arm and 20 in the PSS-alone arm. Mean time from arrival in the room until groin puncture was 61.9±14.0 min in the RAL group and 51.2±10.8 min in the PSS-alone group (P=0.01; difference=10.7 min). Patients in the PSS-alone group reported less pain than those in the RAL group. Furthermore, anesthetists reported accurate blood pressure in the PSS group. The average cost estimate of RAL placement was US$774.70, with a range of US$743 to US$1171. Conclusions: Placement of a RAL at the start of the neuroendovascular procedures resulted in increased delays to procedure start time and more patient-reported pain compared with the PSS, which may offer a more efficient means of blood pressure monitoring for neurointerventional procedures. Clinical trial registration: NCT03239847.